Between Law and Reality: The Implementation Gaps of Indonesia’s Domestic Violence Law - Sukendar Sukendar (Indonesian State Law Review (ISLRev), 2026)
This study examines the implementation gaps of Indonesia’s Law No. 23 of 2004 on the Elimination of Domestic Violence (DV Law) using a library research method that integrates doctrinal and socio-legal analysis. The findings reveal both substantive and procedural weaknesses that hinder the law’s effectiveness. Substantively, the DV Law lacks clarity in defining psychological and economic violence, imposes lenient penalties, and remains unharmonized with related legal instruments, including the Criminal Procedure Code (KUHAP) and the Sexual Violence Law. Procedurally, inconsistent interpretations among law enforcers, overreliance on visum et repertum (VeR) as primary evidence, limited counselling enforcement, and weak legal socialization restrict victims’ access to justice. Culturally, patriarchal and religious norms continue to normalize domestic abuse as a private matter rather than a public crime. To address these gaps, the study recommends clearer legal definitions, standardized procedures for visum et repertum, institutionalized counselling programs, continuous gender-sensitive training for law enforcers, and broader public education. Ratifying the Optional Protocol to CEDAW is also essential to strengthen state accountability and align Indonesia with global human rights standards. Through doctrinal reform, institutional capacity, and cultural transformation, the DV Law can evolve from a symbolic statute into an effective instrument of substantive gender justice.